The mammalian complement system as an epitome of host–pathogen genetic conflicts. Issue 6 (March 2016) - Cagliani, Rachele; Forni, Diego; Filippi, Giulia; Mozzi, Alessandra; De Gioia, Luca; Pontremoli, Chiara; Pozzoli, Uberto; Bresolin, Nereo; Clerici, Mario; Sironi, Manuela
Abstract: The complement system is an innate immunity effector mechanism; its action is antagonized by a wide array of pathogens and complement evasion determines the virulence of several infections. We investigated the evolutionary history of the complement system and of bacterial‐encoded complement‐interacting proteins. Complement components targeted by several pathogens evolved under strong selective pressure in primates, with selection acting on residues at the contact interface with microbial/viral proteins. Positively selected sites in CFH and C4BPA account for the human specificity of gonococcal infection. Bacterial interactors, evolved adaptively as well, with selected sites located at interaction surfaces with primate complement proteins. These results epitomize the expectation under a genetic conflict scenario whereby the host's and the pathogen's genes evolve within binding avoidance‐binding seeking dynamics. In silico mutagenesis and protein–protein docking analyses supported this by showing that positively selected sites, both in the host's and in the pathogen's interacting partner, modulate binding.